Analisis dan Perancangan Aplikasi Penilaian Kesehatan KSP dan USP Pada DInas Koperasi Kabupaten Sidoarjo - Pramadita, Ventya Devi; Setyawan, Henry Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Currently the Office of Cooperative Sidoarjo regency, especially in the Seksi Bina Usaha Simpan Pinjam experienced a problem that is on the dimension of time is the amount of data that must be processed, the process of health assessment done manually, and there was no warning system regarding Koperasi Simpan Pinjam (KSP) or Unit Simpan Pinjam (USP) who have not submitted reports Rapat Anggota Tahunan (RAT). On the dimension of content is input weighting process aspect, the process of checking the standard tables assessment is done manually. Based on these problems, needs analysis and design application health assessment KSP/USP. Analysis and design are expected to produce a document on which to base the development of software applications health assessment KSP/USP. After the application design was developed to help the Department of Cooperatives Sidoarjo District to provide the required information, and assessing the health of the KSP and USP. After analysis and application design health assessment KSP/USP of this, it can produce documents in the form of Software Requirement Specification (SRS) and Software Architecture and Design (SAD). The document can be used as the basis for the development of software applications health assessment KSP/USP. Keywords: Health Assessment, KSP and USP, analysis and design , SRS and SAD documents.